Pembangunan yang Responsif Gender melalui Musrenbang di Kabupaten Konawe - Sartiah Yusran (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This survey aims to determine the extent of understanding and knowledge of the women and the poor people about the importance of their involvement in the development and their understanding of their rights to participate in development through Musrenbang, as well as their expectations about the next steps. This survey focused on women and the poor in Konawe as the sample and population who have been determined from several representative that representing several districts of UNDP work areas (5 districts). The survey results indicate several things, namely: a) the term